Expression and localization of the multidrug resistance proteins MRP2 and MRP3 in human gallbladder epithelia - König, Jörg; et al. (Gastroenterology, 2001)
Background & Aims: The multidrug resistance protein (MRP) isoforms MRP2 (ABCC2) and MRP3 (ABCC3) play a decisive role in the hepatic secretion of endogenous and xenobiotic conjugates and are differentially expressed in hepatocytes and cholangiocytes. The epithelium of the gallbladder considerably modifies the composition of primary hepatic bile by absorption and secretion; however, the underlying transport mechanisms were largely unknown. Localization of MRP2 and MRP3 may provide an explanation of how the products of phase II conjugation are effluxed from gallbladder epithelia. Methods: Expression and localization of MRP2 and MRP3 were analyzed by reverse-transcription polymerase chain reaction (RT-PCR) and immunofluorescence microscopy of human gallbladder tissue. Results: Expression of MRP2 and MRP3 was identified in all gallbladders by RT-PCR followed by sequencing of the amplified fragments. Double immunofluorescence microscopy using 2 specific antibodies for the respective MRP isoform showed the simultaneous expression of MRP2 in the apical membrane and MRP3 in the basolateral membrane of gallbladder epithelia. MRP1 protein expression was not detectable. Conclusions: Our findings show the expression of MRP2 and MRP3 in distinct plasma membrane domains of gallbladder epithelia and provide evidence for the capacity of the gallbladder to secrete xenobiotic and endogenous anionic conjugates into blood via MRP3 and into bile via MRP2.
Created from Fastlane, Scopus look-up